Quantifying in vivo murine antigen-specific T cell responses without requirement for prior knowledge of antigen identity. Issue 2 (April 2017) - Kibbi, Nour; Hong, Enping; Ezaldein, Harib; Hanlon, Douglas; Fahmy, Tarek; Edelson, Richard
Abstract: Extracorporeal Photochemotherapy (ECP) is a widely applied anti-cancer immunotherapy for patients with cutaneous T cell lymphoma (CTCL). By using apoptotic malignant cells as a source of patient-specific tumor antigen, it enables clinically relevant and curative anti-CTCL immunity, with potential efficacy in other tumors. Currentmethods to track patient-specific responses are tedious, and new methods are needed to assess putative global immunity. We developed a clinically practical method to assess antigen-specific T cell activation that does not rely on knowledge of the particular antigen, thereby eliminating the requirement for patient-specific reagents. In the OT-I transgenic murine system, we quantified calcium flux to reveal early T cell engagement by antigen presenting cells constitutively displaying a model antigenic peptide, ovalbumin (OVA)-derived SIINFEKL. We detected calcium flux in OVA-specific T cells, triggered by specific T cell receptor engagement by SIINFEKL peptide-loaded DC. This approach led to sensitive detection of antigen-specific calcium flux (ACF) down to a peptide-loading concentration of ∼10 −3 uM and at a frequency of ∼0.1% OT-I cells among wild-type (WT), non-responding cells. Antigen-specific T cells were detected in spleen, lymph nodes, and peripheral blood after adoptive transfer into control recipient mice. Methods like this for assessing therapeutic response are lacking in patients currently on immune-based therapies, such as ECP, where assessment of clinical response is made by delayed measurement of the size of the malignant clone. These findings suggest an early, practical way to measure therapeutically-induced anti-tumor responses in ECP-treated patients that have been immunized against their malignant cells.